Housing Wealth and Consumption Growth: Evidence from a Large Panel of Households - Gan, Jie (Review of Financial Studies, 2010)
[This article uses a large panel dataset that tracks the housing wealth and credit card spending of 12,793 individuals in Hong Kong to study the relationship between housing wealth and household consumption. I identify a significant effect of housing wealth on consumption. A pure wealth effect can explain part of the sensitivity: households with multiple houses have much stronger consumption responses. Consistent with a relaxation of the credit constraints, mortgage refinancing significantly increases households' consumption sensitivities. However, for the majority of the households that do not refinance, consumption sensitivity appears to be due to a reduction in precautionary saving.]